RECOVERY STRATEGIES IN SPORT - A REVIEW OF CURRENT RESEARCH - Karolina Wojdat-Krupa,; Weronika Ossowska,; Maksymilian Czarnota,; Monika Rogowska,; Klaudia Płudowska,; Julia Dolinkiewicz,; Karol Sikora,; Aleksandra Przelaskowska,; Paulina Lewaśkiewicz, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Effective recovery is critical for optimizing athletic performance and preventing injury. This review aims to synthesize current research on recovery strategies in sport by examining the physiological, neurological, and psychological mechanisms underlying fatigue and regeneration.Key findings: The multifactorial nature of fatigue is discussed, including metabolic, central, and peripheral contributors, as well as individual differences related to age and sex. Cellular and systemic regenerative processes are analyzed to understand recovery dynamics. Popular recovery methods such as sports massage, cryotherapy, balneotherapy, and hydrotherapy are evaluated alongside nutritional interventions including protein, carbohydrates, creatine, BCAAs, caffeine, and vitamin D supplementation. The role of sleep and neuropsychological recovery techniques, including breathing exercises, is emphasized. Emerging trends such as active recovery protocols and the application of wearable technology—particularly heart rate variability (HRV) monitoring—are reviewed for their potential to personalize and enhance recovery.Conclusions: A holistic, individualized approach to recovery that integrates physiological, nutritional, and technological strategies is essential for maximizing athletic outcomes. Despite advances, significant gaps remain in understanding the optimal combination and timing of recovery interventions, highlighting the need for further rigorous research.